Comprehensive Analysis of the Soybean (Glycine max) GmLAX Auxin Transporter Gene Family - Chai, Chenglin; Wang, Yongqin; Valliyodan, Babu; Nguyen, Henry T. (Frontiers in Plant Science, 2016)
The phytohormone auxin plays a critical role in regulation of plant growth and development as well as plant responses to abiotic stresses. This is mainly achieved through its uneven distribution in plants via a polar auxin transport process. Auxin transporters are major players in polar auxin transport. The AUXIN RESISTANT 1 ⁄ LIKE AUX1 (AUX⁄LAX) auxin influx carriers belong to the amino acid permease family of proton-driven transporters and function in the uptake of indole-3-acetic acid (IAA). In this study, genome-wide comprehensive analysis of the soybean AUX⁄LAX (GmLAX) gene family, including phylogenic relationships, chromosome localization, and gene structure, were carried out. A total of 15 GmLAX genes, including seven duplicated gene pairs, were identified in the soybean genome. They were distributed on 10 chromosomes. Despite their higher percentage identities at the protein level, GmLAXs exhibited versatile tissue-specific expression patterns, indicating coordinated functioning during plant growth and development. Most GmLAXs were responsive to drought and dehydration stresses and auxin and abscisic acid (ABA) stimuli, in a tissue- and/or time point- sensitive mode. Several GmLAX members were involved in responding to salt stress. Sequence analysis revealed that promoters of GmLAXs contained different combinations of stress-related cis-regulatory elements. These studies suggest that the soybean GmLAXs were under control of a very complex regulatory network, responding to various internal and external signals. This study helps to identity candidate GmLAXs for further analysis of their roles in soybean development and adaption to adverse environments.